Coffee shop dan gaya hidup mahasiswa perkotaan - Hapsari, Zhaqiya Rizqy; Wijaya, Atika (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: This article discusses the Coffee Shop and urban student lifestyle. The emergence of Coffee Shops is currently booming in big cities, one of which is Semarang City. Findings: The phenomenon of the rise of the Coffee Shop is currently being used for various purposes by all circles of society, one of which is as a student. The purpose of writing this article is to find out the background of students who like to visit Coffee Shops, and the changes in the lifestyle of students who are Coffee Shop fans. Methods: The research in this article uses a qualitative method with the subjects of Semarang State University (UNNES) students who like to visit Coffee Shops. The data collection techniques were carried out by observation, interviews, and documentation. Articles are presented in descriptive form using consumption theory and lifestyle concepts. Conclusion: The results of the study indicate that there are several factors behind the student's fondness for visiting Coffee Shops, including: place factors, menu variations and tastes, friendship environment and social media. The interest of students in visiting these certainly causes a change in the lifestyle felt by students who are fans of Coffee Shops, namely: sleeping patterns, tastes in places to eat, appearance or clothing, active social media, and consumptive behavior.